2020
DOI: 10.3390/ijms21176344
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Disease-Associated Tau Impact on Mitochondria

Abstract: Abnormal tau protein aggregation in the brain is a hallmark of tauopathies, such as frontotemporal lobar degeneration and Alzheimer’s disease. Substantial evidence has been linking tau to neurodegeneration, but the underlying mechanisms have yet to be clearly identified. Mitochondria are paramount organelles in neurons, as they provide the main source of energy (adenosine triphosphate) to these highly energetic cells. Mitochondrial dysfunction was identified as an early event of neurodegenerative diseases occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 176 publications
3
56
0
2
Order By: Relevance
“…Wang et al (2009) showed that when K18 tau with the K280 mutant (Tau RD K) is expressed in N2a cells, Tau RD K interacts with LAMP-2A in lysosome and is thereby processed to highly amyloidogenic fragments which nucleate aggregation of tau. Growing evidence suggests that mitochondrial dysfunction is closely related to the pathophysiology of tauopathies (Szabo et al, 2020;Wang et al, 2020). Phosphorylated tau is also found at the mitochondria membrane (Jancsik et al, 1989;Rendon et al, 1990).…”
Section: The Association Of Tau With Intracellular Organelle Membranementioning
confidence: 99%
“…Wang et al (2009) showed that when K18 tau with the K280 mutant (Tau RD K) is expressed in N2a cells, Tau RD K interacts with LAMP-2A in lysosome and is thereby processed to highly amyloidogenic fragments which nucleate aggregation of tau. Growing evidence suggests that mitochondrial dysfunction is closely related to the pathophysiology of tauopathies (Szabo et al, 2020;Wang et al, 2020). Phosphorylated tau is also found at the mitochondria membrane (Jancsik et al, 1989;Rendon et al, 1990).…”
Section: The Association Of Tau With Intracellular Organelle Membranementioning
confidence: 99%
“…Several studies have reported that amyloid precursor protein (APP) and Aβ localize to mitochondria, and Aβ appears to act as a mitochondrial toxin [78][79][80][81][82][83][84][85]. The tau protein also appears to localize to mitochondria and contribute to mitochondrial dysfunction through multiple mechanisms [86][87][88][89][90][91][92]. Similarly, a cleavage product from the apolipoprotein E protein displays a mitochondrial localization signal, targets mitochondria, and inhibits COX activity [93,94].…”
Section: Mitochondria In Admentioning
confidence: 99%
“…tive damage to the central nervous system. The results showed that the expression of human tau protein could cause the dynamic imbalance of mitochondrial division and fusion between HEK293 cells and primary neurons, and the neuronal process was significantly shortened and the cell viability decreased [24] . Damage to mitochondrial function can affect mitochondrial endoplasmic reticulum…”
Section: Tau Proteins Affect Mitochondrial Dysfunctionmentioning
confidence: 99%